A representação simbólica no Livro das aves do Lorvão - Silva, Rosângela Nobre da (2023)
This study analyzes the symbolic bird representation in the Lorvão Book of Birds, an illuminated manuscript produced in the 12th century, very popular in medieval Europe. The work consists of a kind of rules and conduct handbook that was used, in the Middle Ages, for didactic purposes, with the goal of guiding the monks who lived in the monasteries to follow the Christian way. In order to do that, the manuscript makes use of the birds to extract from them a message, with a symbolic nature, facing an allegorical Christian interpretation. Thus, its textual content consists in a literal description of the bird, followed by a moral background interpretation, usually with a reference to the biblical text. In this sense, this research aims to translate and analyze the treatises referring to the birds Pelican, Jackdaw, Corvo, Cock and Ostrich, covered by the chapters 38 to 42 of the book, with emphasis on the description of the vices and virtues identified in the behavior of the birds. Therefore, it can be noted that some birds show virtues, like the pelican, which, just as the Christ, sacrificed its own flesh to give life to its sons. Others, however, sometimes represent the sacred, sometimes they present conduct related to the profane, such as the crow, which, on the one hand, symbolizes a bad pressage, but, on the other hand, represents cunning, fertility and wisdom. As for the theoretical support, this study is based on Maciel (2008), who inserts the animals into the field of the Zoo-literature and look into the relations that exist between the human and the non-human; as well as Pliny the Elder (79 A.D.), Isidore of Seville (1479-1530) and Varandas (2006), who are essential sources related to the medieval bestiaries nature, object of this study. Regarding the source of the text in Latin, the edition by Willene B. Clark (1992) was used.